Associated factors to develop traumatic events in the future: Young Lives analysis - Quiroz Portella, Rafael (2018)
Introduction: Until now most of the research involving intelligence and associated factors to suffer traumatic events (TE) comes from research done in adults or in children from developed countries, from refugee camps or survivors of a war, terrorism or natural disasters. Much less information is available on longitudinal studies with community-based samples of children from low and middle income countries out of these specific events. Objective: To determine the association between intelligence and other factors to suffer TE in Young Lives (YL) children of two low-middle income countries: India and Peru. Methods: We did a secondary analysis of Young Lives cohort Study which included 1669 children around 8 years old of age from India and Peru. YL uses a clustered-stratified, multi-stage, random sampling per country. Upon recruitment, children´s intelligence was assessed applying the Raven’s Colored Progressive Matrices Test and the child´s caregivers were asked about socio-demographic factors. On follow up, 4 years later the caregivers were asked about the occurrence of TE in their child. Robust Poisson Regression was used for the multivariate analysis. Results: Around 20% of children in the study had suffered TE. Intelligence was not related to suffer future TE. Living on rural areas have 49% more risk of suffering a TE compared to urban locations. Children with history of past TE had 40% more risk of suffering another TE during follow-up. Finally, no association was found between TE and other socio-demographic variables. Conclusions: Intelligence was not an associated factor for future TE on YL children from India and Peru. But living on rural locations and having the history of TE were both risk factors.